Diskursus Pemikiran Politik Islam Dari Era Klasik Hingga Pertengahan : Studi Pemikiran Al-Mawardi dan Ibn Taimiyyah - S Supian (Politea : Jurnal Politik Islam, 2020)
This paper describes the development of Islamic political thought during the classical and medieval times represented by Al-Mawardi and Ibn Taimiyah. Al-Mawardi who focused more on the Islamic government system, while Ibn Taymiyyah focused more on the goals of an Islamic government. In the contemporary context, the thoughts of these two figures can complement the discussion, especially when groups who want the establishment of an Islamic government based on the caliphate system. Practical values ??that have been shown in the history of Islamic politics, starting from the time of the Prophet Muhammad, the elected and elected Caliph Abubakar al-Shiddiq and consensus, the Caliph Umar Ibn al-Khattab who was appointed directly by the Caliph Abubakar, the Caliph Usman Ibn Affan who elected through the formatur path, Caliph Ali Ibn Thalib who was elected through a representative system, until the establishment of the caliphate system by the Umayyads, Bani Abbsiyah, Islamic political upheaval in classical times, medieval times, to the history of democratic and modern Islamic countries. All of them show that it is certain that there is no single system or standard form that must be adopted by Islam, to become the only ideal government or Islamic state.